2022
DOI: 10.3390/v14030647
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Norovirus Infections and Their Association with Childhood Growth: Findings from a Multi-Country Birth Cohort Study

Abstract: The prevalence of norovirus infections in different geographical locations and their attribution to childhood diarrhea is well established. However, there are no reports showing possible relationships of different norovirus genogroups with subsequent childhood malnutrition. In this study, we attempted to establish a potential association between asymptomatic norovirus infections with childhood growth faltering during. Non-diarrheal stools were collected from 1715 children enrolled in locations in a multi-count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…These ndings underscore the importance of preventive measures such as hand hygiene and public health interventions to reduce the burden of NoV infections. This nding is in agreement with different studies (22,48).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These ndings underscore the importance of preventive measures such as hand hygiene and public health interventions to reduce the burden of NoV infections. This nding is in agreement with different studies (22,48).…”
Section: Discussionsupporting
confidence: 94%
“…While these viruses typically cause mild and selflimiting acute infections, studies suggest that long-term infections are common among high-risk groups (20,21). Factors such as a history of contact with individuals with similar AGE, inadequate hand hygiene, lack of access to clean drinking water, consumption of raw food, absence of improved sanitation facilities, and poor environmental hygiene have been associated with an increased risk of HuCV (17,22).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the association of norovirus AGE and living in a household with dirt floors was not unexpected, as norovirus particles have been shown to persist on floors as dust [ 18 , 19 ], and it is conceivable that porous dirt floors would be harder to disinfect than tile or other hard-surface flooring. A prior study in eight LMICs showed that improved flooring as well as higher LAZ was protective against norovirus infection in the first two years of life [ 12 ]. Our study did not collect extensive data on, and thus did not identify nutrition practices that were associated with norovirus; this could be the focus of future studies that are designed to accurately capture a diverse range of food and beverage consumption among children at risk for norovirus.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies from LMIC using cross-sectional, cohort, and case–control designs have reported that younger age, larger households, household sanitation and socioeconomic factors, eating outside the household, and having contact with another household member with AGE symptoms were risks for norovirus AGE, while studies were mixed on the benefits of breastfeeding in reducing norovirus AGE [ 8 , 9 , 10 , 11 , 12 ]. The goal of this study was to identify modifiable risk factors for norovirus AGE in a population of young Nicaraguan children, using a larger sample of symptomatic norovirus-infected children than in previous studies and assessing previously unstudied risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the studies have correlated these non-invasive biomarkers with the composite EED score that has been proposed based on neopterin (NEO), myeloperoxidase (MPO), and alpha-1 anti-trypsin (A1AT) to diagnose EED and the findings were published earlier 7 . Several studies have also used this composite score for the better prediction of EED and intestinal inflammation [8][9][10][11][12][13] . In addition, EED score has also been found to be correlated with LCN2 in our previously published cross-sectional study in Bangladesh 14 .…”
mentioning
confidence: 99%